Estimating the Macroeconomic Effects of Oil Supply News - Lorenzo Mori; Gert Peersman (CESifo GmbH, 2024)
A common approach for estimating the macroeconomic effects of oil supply news employs SVAR-IV models identified using changes in oil futures prices around OPEC quota announcements as an instrument. However, we show that the reduced-form oil price innovations, structural shocks, and the instrumental variable in these estimations are all Granger-caused by financial variables, indicating informational deficiencies in the VAR model and contamination of the instrument. To resolve these issues, we incorporate financial indicators into the econometrician's information set, yielding significantly different results. These include a sharper short-term output decline, lower and less persistent inflationary effects, and a reversal of the monetary policy response. Our results also show greater stability over time and the disappearance of puzzling responses. Finally, we identify similar issues in other prominent oil-market SVAR models, suggesting that informational deficiencies are a pervasive issue in oil-market research.
Keywords: C32; C36; E31; E32; F31; Q43; 330; oil supply news shocks; OPEC announcements; SVAR-IV; informational deficiencies